The Concept of Islamic Education According to the Views of Imam Al-Ghazali - Ibnu Fiqhan Muslim; Priyono; Apipudin; Ranam, Sanudin (CV ODIS, 2024)
This article aims to analyze Al-Ghazali's views regarding Islamic education. In this research, library research methods were used to review Al-Ghazali's thoughts and conceptions regarding Islamic education. The findings from this research show that Al-Ghazali has a deep understanding of Islamic education. Apart from that, this article discusses his views regarding educational management, student management, and curriculum preparation. In conclusion, Al-Ghazali views education as a process to develop humans towards perfection, with a spiritual approach to achieving good life goals. This article also details the aspects that need to be fulfilled by students, such as appreciating learning as a spiritual process, concentration, and an attitude of humility. Regarding the curriculum, Al-Ghazali emphasized the importance of religious knowledge and ethics, based on two main tendencies: the religious and Sufism tendency and the pragmatic tendency.